A population-based and case-controlled study of children and adolescents with narcolepsy: Health-related quality of life, adaptive behavior and parental stress. (March 2019) - Szakács, Attila; Chaplin, John Eric; Tideman, Pontus; Strömberg, Ulf; Nilsson, Jannie; Darin, Niklas; Hallböök, Tove
Abstract: Objective: To investigate health-related quality of life (HrQoL) and adaptive behavior in young people with narcolepsy and stress among their parents. Methods: In a cross-sectional exploratory quantitative study design, 37 young people with narcolepsy (8–20 years of age) and their parents were recruited. Thirty-one had post-H1N1 vaccination-related narcolepsy (PHV) and six had narcolepsy not related to PHV (nPHV). In addition, 40 age- and gender-matched controls (aged 5–20 years) were recruited. Results: Thirty-one patients completed the generic HrQoL questionnaire KIDSCREEN and the disease-specific NARQoL-21. HrQoL was found to be significantly diminished in all domains in the PHV group (p = 0.001) and in the School/Concentration domain (p = 0.004) in the nPHV group compared to age- and gender-matched controls. The Adaptive Behavior Assessment System was completed by parents of 32 patients. They rated their children significantly lower in the General adaptive composite (p = 0.026) and the Conceptual (p = 0.050) and Social composite scores (p = 0.001) compared with reference data on healthy Swedish children's and young people's adaptive behavior. Parents of 36 patients filled in the 36-item short form of the Parenting Stress Index questionnaire. They rated significantly higher Total stress, Parent-child dysfunctional interaction, and Difficult child scores compared with parents of controls (p = 0.001, p = 0.005, p < 0.001). Conclusions: Children with narcolepsy have diminished HrQoL compared with controls. Parents of children with narcolepsy experience impaired adaptive behavior in their children and high levels of parenting stress. Identifying the contributory factors is necessary, and early intervention is crucial in order to improve the HrQoL of these children and their families. Highlights: We studied 37 children with narcolepsy. Generic and disease-specific health-related quality of life was decreased in all domains compared with healthy controls. Parents noted lower adaptive behavior in their child compared with general population and increased parenting stress compared with healthy controls. Psychiatric comorbidity had a negative impact on all of the study variables examined.